2000
DOI: 10.1007/s005350070004
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter therapy of gastric cancer metastatic to the liver: preliminary results

Abstract: Little is known about the effectiveness of transcatheter chemotherapy in liver metastases from gastric cancer. The aim of this study was to evaluate the initial results of hepatic artery infusion and oily chemoembolization in these liver secondaries. Courses of transcatheter arterial infusion with 5-fluorouracil/ doxorubicin (12 patients) and oily chemoembolization with doxorubicin-in-iodized oil and gelatin sponge (12 patients) were performed in 24 patients with histologically proven unresectable gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Also, embolization is useful in the presence of an associated vascular lesion as an AV malformation, fistula, or a hemangioma. HAI, TAE and TACE have shown promising symptomatic, morphological and survival results in liver metastases from other primary tumours, like malignant melanoma, neuroendocrine and carcinoid tumours, breast and gastric cancer [22,23,28,29,[33][34][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…Also, embolization is useful in the presence of an associated vascular lesion as an AV malformation, fistula, or a hemangioma. HAI, TAE and TACE have shown promising symptomatic, morphological and survival results in liver metastases from other primary tumours, like malignant melanoma, neuroendocrine and carcinoid tumours, breast and gastric cancer [22,23,28,29,[33][34][35][36][37][38][39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…The use of TACE and laser induced ablation as treatment for non-colorectal and non-breast cancer liver metastases in our patients showed a mean survival of 40.8 months. Whereas in studies dealing with the use of TACE alone in similar patient groups showed lower survival times (5-21 months), with extended survival of up to 60 months in studies concerning only neuroendocrine primaries [10,20,23]. Results for the use of ablative techniques alone in the treatment of liver metastases have shown survival times of up to 48 months in patients treated with LITT and up to 37 months for radiofrequency ablation.…”
Section: Discussionmentioning
confidence: 98%
“…Still it is important to notice that the current treatment regimen should not be regarded as an alternative to surgery and should be reserved only to unresectable patients not responding to systemic chemotherapy. Untreated patients present with a median survival of 2-8 months [6,20,21]. Furthermore, TACE treatments induce a high local concentration of chemotherapeutic agents with a lower systemic toxicity than systemic chemotherapy regimes.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary liver metastasis was then diagnosed by integral analysis of the disease history, laboratory findings and abdominal CT imaging. Although surgical resection remains as a curative treatment for hepatic metastastic cancer, transcatheter arterial chemoembolization (TACE) has become an effective option for those unresectable liver metastases from pancreatic carcinoid tumor, gastric, colorectal, or breast cancers [13][14][15][16] . In view of the rich blood supply of liver metastatic carcinomas as well as the poor condition in this aged patient, a selective TACE was performed to prolong survival.…”
Section: Discussionmentioning
confidence: 99%